2010
DOI: 10.1186/1746-6148-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary hematopoiesis in a case of benign mixed mammary tumor in a female dog: cytological and histopathological assessment

Abstract: BackgroudExtramedullary hematopoiesis (EMH) is defined as the presence of hematopoietic stem cells such as erythroid and myeloid lineage plus megakaryocytes in extramedullary sites like liver, spleen and lymph nodes and is usually associated with either bone marrow or hematological disorders. Mammary EMH is a rare condition either in human and veterinary medicine and can be associated with benign mixed mammary tumors, similarly to that described in this case.Case presentationHematopoietic stem cells were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In humans, EMH has been reported in association with cerebellar hemangioblastoma, astrocytoma, hemangioma, hepatoblastoma, leiomyoma, pilomatricoma, hepatic angiosarcoma, endometrial carcinoma, meningioma, hepatic adenoma, spindle cell lipoma, liposarcoma, myofibroblastic tumors, and renal tumors. 78 EMH has been reported in up to 42% of hemangiosarcomas in dogs, 6 in a benign mixed mammary tumor in a dog, 30 and in histiocytic sarcomas in mice and dogs. 57,71 We have observed EMH in cytologic specimens from histiocytic sarcomas in dogs (Fig.…”
Section: Emh Within Neoplasmsmentioning
confidence: 99%
“…In humans, EMH has been reported in association with cerebellar hemangioblastoma, astrocytoma, hemangioma, hepatoblastoma, leiomyoma, pilomatricoma, hepatic angiosarcoma, endometrial carcinoma, meningioma, hepatic adenoma, spindle cell lipoma, liposarcoma, myofibroblastic tumors, and renal tumors. 78 EMH has been reported in up to 42% of hemangiosarcomas in dogs, 6 in a benign mixed mammary tumor in a dog, 30 and in histiocytic sarcomas in mice and dogs. 57,71 We have observed EMH in cytologic specimens from histiocytic sarcomas in dogs (Fig.…”
Section: Emh Within Neoplasmsmentioning
confidence: 99%
“…Bone formation occurs via the endochondral ossification of pre-existing cartilage formed by the differentiation of myoepithelial cells or the intramembranous ossification of the connective tissue of the stroma (27). The presence of bone marrow with haematopoietic tissue and intermingled adipose tissue are observed in some cases (2,28).…”
Section: Bmtsmentioning
confidence: 99%
“…Recently, Grandi et al (2010) reported a case of extramedullary hematopoiesis in a benign mixed mammary tumor of a dog. Cytological analysis, prior to surgical resection of the tumor, showed hematopoietic young, mature and precursors cells, such as rubriblasts, myeloblasts, promyelocytes, megakaryocytes, prorubricytes, rubricytes, metarubricytes, erythrocytes, and a discrete quantity of osteoclasts.…”
Section: Discussionmentioning
confidence: 98%